Strategies on fall prevention for older people living in the community: A report from a round-table meeting in IAGG 2013 - Kim, E.; Arai, H.; Chan, P.; Chen, L.; Hill, Keith; Kong, B.; Poi, P.; Tan, M.; Yoo, H.; Won, C. (Elsevier, 2015)
Copyright © 2015, Asia Pacific League of Clinical Gerontology & Geriatrics. Abstract Over the past decade, a number of programs and strategies have been proposed and developed in an effort to reduce risks among the elderly in relation to falling or sustaining fall related injuries. Programs vary in their approach, and also in their target populations. We held a round-table meeting to present each country's research data on fall prevention in older people and summarized them in order to formulate evidence-based suggestions on the prevention of falls in older people. Although the contents and level of progress of each country's studies had some differences with regards to fall prevention, the social issues of fall prevention was of particular interest in large scale cohorts studies and fall prevention guidelines. We recommended some good practice points for the strategies on fall prevention for older people living in the community based on clinical experience or expert consensus.